AN ANALYSIS OF DEIXIS USING “BEAUTY AND THE BEAST” MOVIE SCRIPT - Elisa Fadlilah; Rika Septyani (IKIP Siliwangi, 2018)
This study deals with the English deixis. The objectives of this study are to analyze type of deixis and to find out the frequency of each deixis in the movie entitled Beauty and The Beast. This study was conducted by using descriptive qualitative research. The source of data was taken from the movie script of Beauty and The Beast. Documentary technique is used in collecting data. The findings showed that there are three types of deixis found in the Beauty and The Beast movie script and there are nine frequencies of deixis, namely person deixis in greater occurrences than another. Type of person deixis is used 128 times or (84,21%), which consists of first person used 53 times or (34,86 %), second person used 52 times or (34,21 %), and third person used 23 times or (15,13 %). The next, spatial (place) deixis is used 12 times or (7,89 %) and the last, temporal (time) deixis is used 12 times or (7,89 %) which consists of present used 5 times or (3,28 %), past used 5 times or (3,28 %), future used 2 times or (1,31 %). The least frequently used by the Beast in Beauty and the Beast Speech film`s dialogue was first person deixis used 53 times or (34,86 %). Keywords: Pragmatic, Movie, Deixis